Multi-objective Optimal Dispatch of Off-grid Integrated Hydrogen Energy Utilization System - Zhu Shihao; Hu Hongming; Du Banghua; Xie Changjun; Zhu Wenchao (E3S Web of Conferences)
The integrated hydrogen energy utilization system (IHEUS) exhibits great potential for microgrid applications. However, its practical application faces significant challenges mainly due to the low energy conversion efficiency and rapid aging of the electrolyzers and fuel cells, especially when handling highly fluctuating power flows. To this end, this study proposes a multi-objective optimal dispatch scheme for off-grid IHEUS operations, where waste heat recovery and life cycle cost are taken into consideration to address the above problems. We first establish a first-principle model that describes the electric-hydrogen-heat output characteristics of the system, where the waste heat recovery and utilization systems have been focused. By correlating the aging behaviors and lifetime to voltage degradation, a life-cycle operational cost function is derived for a multi-objective optimization (MOO) model. In this MOO model, we adopt comprehensive energy efficiency and energy supply loss probability as the performance evaluation and optimization criteria so as to improve energy efficiency and supply stability, and the designed MOO problem is solved and ranked by a proposed NSGA-III joint entropy-weighted TOPSIS strategy. Comprehensive comparative studies exhibit that this proposed NSGA-III joint entropy-weighted TOPSIS strategy can effectively determine the optimal operation dispatch scheme. Consequently, a 46.13% reduction in operating costs can be achieved at the same the comprehensive energy efficiency and ESLP.